If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + -9(13t + -1) = 6(-20t + -10) Reorder the terms: -9 + -9(-1 + 13t) = 6(-20t + -10) -9 + (-1 * -9 + 13t * -9) = 6(-20t + -10) -9 + (9 + -117t) = 6(-20t + -10) Combine like terms: -9 + 9 = 0 0 + -117t = 6(-20t + -10) -117t = 6(-20t + -10) Reorder the terms: -117t = 6(-10 + -20t) -117t = (-10 * 6 + -20t * 6) -117t = (-60 + -120t) Solving -117t = -60 + -120t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '120t' to each side of the equation. -117t + 120t = -60 + -120t + 120t Combine like terms: -117t + 120t = 3t 3t = -60 + -120t + 120t Combine like terms: -120t + 120t = 0 3t = -60 + 0 3t = -60 Divide each side by '3'. t = -20 Simplifying t = -20
| 5n+22=22 | | 3(f-2)=7(f+2) | | C+5-2x=3+x | | -4y+b= | | 4(x+5)=-4x-20 | | 12n+22=5 | | 18d+18+20=2(15d-17) | | 5(x+1)-6x=-11x | | f(p)=p^2-6p+1 | | y=3500x+31500 | | y-14=y | | 2.8v-3.54-17.4v=-9.19-15.1v | | 12n+22=44 | | (x-3/2)^2-5/4=0 | | 10-5s=-10-3s | | (2x-7)/5=4⋅(x-2) | | 5(2k+3)-8=6p+29 | | 12n+22=128 | | 0.0003x=1 | | 16.2s-16.76=16.7s-15.26 | | 10d=9+9d | | 12n+22=125 | | m-2/3=-1/2 | | 15-3h=2h+2 | | -10.8n+5.16=-11.2n | | -6c-6=-5c | | (x-3/2)2-5/4=0 | | 0.45+15.1k=18.3+16.8k | | x(3x+3)=0 | | 109=-7+18 | | -x-4x=20 | | -16-(-2m)=8m+12 |